The load-velocity profiles of three upper-body pushing exercises in men and women - García-Ramos, A.; Suzovic, D.; Pérez-Castilla, A. (Sports Biomechanics, 2021)
This study aimed to explore the differences in the load-velocity profile between three upper-body pushing exercises in men and women. The load-velocity profiles (from 20% to 100% of the one-repetition maximum [1RM] in 5% increments) of 24 sport sciences students (12 men) were randomly tested during the horizontal bench press (HBP), inclined bench press (IBP) and seated military press (SMP) exercises. The 1RM was higher for the HBP (men: 94.2 ± 14.6 kg; women: 45.4 ± 10.1 kg), followed by the IBP (men: 87.7 ± 11.6 kg; women: 41.6 ± 6.6 kg), and finally the SMP (men: 67.4 ± 7.8 kg; women: 37.3 ± 6.3 kg). The mean test velocity (i.e., averaged velocity of all loads) and the slope of the load-velocity profile were significantly different between exercises (SMP > IBP > HBP) and sexes (men > women). The correlations between the exercises were very high for the individual 1RM values (r range = 0.714-0.982), but lower correlations were observed for the mean test velocity (r range = 0.237-0.766) slope of the load-velocity profile (r range = 0.018-0.721), and velocity of the 1RM (r range = 0.004-0.446). These results confirm that men present higher velocities at low relative loads (i.e., %1RM) compared to women during upper-body pushing exercises.